Development Bvag Replication Prototype In Distributed Database Environment - Muhammad Fathul Amin, Sulaiman (2023)
Replication is a useful technique for distributed database systems. Through this technique, a data can be accessed from multiple locations. Thus, it increases data availability and accessibility to users. When one site fails, user still can access the same data at another site. Techniques such as Read-One-Write-All (ROWA), Hierarchical Replication Scheme (HRS) and Branch Replication Scheme (BRS) are the popular techniques being used for replication and data management. However, these techniques have its weaknesses in terms of communication costs. Consequently, ROWA, HRS and BRS take long executing time for a transaction since these techniques have to replicate its data to all servers. In this research, the some-data-to-some-sites scheme called Binary Vote Assignment on Grid (BVAG) is proposed. It works by considering neighbors binary vote assignment to its logical grid structure on fragmented data copies in order to manage transactions in the systems. For simplicity, the neighbours are assigned with vote one or zero. The assignment provides minimum communication cost due to the minimum number of quorum size required. In addition, it minimizes the storage capacity needed since we store database that has been fragmented. The development of prototype for the BVAG replication techniques were carried out using HTML, CSS, JavaScript and PHP. The prototype was developed in order to produce a web-based application that utilize BVAG replication techniques. From the development, the web based BVAG were developed and tested with basic data input to replicate the data. From the results, it shows the web based BVAG prototype is working and able to replicate data to the neighbour’s site.